GE_GERICHTE C/6493/2016 vom 14. Dezember 2018 - GE Cour de justice (2018)
CONCLUSIONS ; NOUVEAU MOYEN DE PREUVE ; LÉGITIMATION ACTIVE ET PASSIVE ; CONTRAT D'ENTREPRISE ; DEMEURE ; RÉSILIATION ; DOMMAGES-INTÉRÊTS | CO.363; CO.366.al1; CO.102ss; CO.108.al1; CO.377